"It's like heaven over there": medicine as discipline and the production of the carceral body - Jason E. Glenn; Alina M. Bennett; Rebecca J. Hester; Nadeem N. Tajuddin; Ahmar Hashmi (BMC, 2020)
Abstract Background Correctional systems in several U.S. states have entered into partnerships with Academic Medical Centers (AMCs) to provide healthcare for people who are incarcerated. This project was initiated to better understand medical trainee perspectives on training and providing healthcare services to prison populations at one AMC specializing in the care of incarcerated patients: The University of Texas Medical Branch at Galveston (UTMB). We set out to characterize the attitudes and perceptions of medical trainees from the start of their training until the final year of Internal Medicine residency. Our goal was to analyze medical trainee perspectives on caring for incarcerated patients and to determine what specialized education and training is needed, if any, for the provision of ethical and appropriate healthcare to incarcerated patients. Results We found that medical trainees grapple with being beneficiaries of a state and institutional power structure that exploits the neglected health of incarcerated patients for the benefit of medical education and research. The benefits include the training opportunities afforded by the advanced pathologies suffered by persons who are incarcerated, an institutional culture that generally allowed students more freedom to practice their skills on incarcerated patients as compared to free-world patients, and an easy compliance of incarcerated patients likely conditioned by their neglect. Most trainees failed to recognize the extreme power differential between provider and patient that facilitates such freedom. Conclusions Using a critical prison studies/Foucauldian theoretical framework, we identified how the provision/withholding of healthcare to and from persons who are incarcerated plays a major role in disciplining incarcerated bodies into becoming compliant medical patients and research subjects, complacent with and even grateful for delayed care, delivered sometimes below the standard best practices. Specialized vulnerable-population training is sorely needed for both medical trainees and attending physicians in order to not further contribute to this exploitation of incarcerated patients.